P-014 Applications of a novel microangioscope for neuroendovascular intervention. (22nd July 2019) - Srinivasan, V; Lazaro, T; Cooper, P; Phillips, M; Garcia, R; Chen, S; Johnson, J; Burkhardt, J; Collins, D; Kan, P
Abstract : Visualization in neuroendovascular interventions relies on biplanar fluoroscopy and digital subtraction. Radiation and contrast-related complications are the two major drawbacks. Angioscopy, direct endoluminal optical visualization, does not require radiation or contrast but has limited utility in neurointerventions due to limitations in size and stiffness. A recently developed microangioscope has the miniaturization and flexibility necessary to navigate small, tortuous intracranial vessels, allowing the practical use of neurovascular angioscopy for the first time. The prototype is a coherent fiber bundle microangioscope embedded in a 0.0165' microcatheter. In human cadaveric experiments, that the microangioscope is compatible with the human intracranial vasculature beyond the Circle of Willis (eg. navigation into and visualization of the M2 origin). In in vivo swine model experiments, the microangioscope has adequate resolution and illumination to identify and differentiate between various intravascular pathologies (eg. red thrombus versus white thrombus). With flow arrest and irrigation, mechanical thrombectomy (both with stent retriever and direct aspiration), coil embolization, stent deployment, and balloon angioplasty were precisely performed under direct visualization with the microangioscope. After deployment, the microangioscope enables direct inspection of devices, providing complementary information to standard angiography. Imaging quality, illumination, and flexibility of the microangioscope progressively improved through modifications to the image bundle. Based on these results, the microangioscope is compatible with the human distal cerebrovasculature; it also provides adequate direct visualization for neurointerventions. Disclosures: V. Srinivasan: None. T. Lazaro: None. P. Cooper: 5; C; Vena Medical, Inc. M. Phillips: 5; C; Vena Medical, Inc. R. Garcia: None. S. Chen: None. J. Johnson: None. J. Burkhardt: None. D. Collins: None. P. Kan: 2; C; Medtronic, Cerenovus.